Canadian urology resident scholarly performance - Andrews, J. Matthew; Abdolell, Mohamed; Norman, Richard W. (Canadian Urological Association Journal, 2013)
Introduction: Scholarly research is a key component of Canadian urology residency. Through comparison of scholarly performance of urology residents before residency with that achieved during residency, we aimed to elicit predictive factors for completion of research activities. Methods: Electronic surveys were sent to 152 urology residents of 11 accredited Canadian programs. Survey questions pertained to post-graduate training year (PGY), formal education, scholarly activity completed before and after the start of residency, protected/dedicated research time, structured research curriculum and pursuit of fellowship training. Results: Surveys were completed by 42 residents from 10 programs. Only 26% of residents had a structured research curriculum, 38% a dedicated research rotation and 43% protected research time. We found that 45% of residents published at least 1 manuscript so far during residency (mean 1.14 ± 0.32), and 43% submitted at least 1 manuscript (mean 0.86 ± 0.25). During residency, 62% of residents completed ≥1 formal research presentation (median number 1.5; range: 0-≥10). Only the level of PGY significantly affected the number of manuscripts published (p < 0.001) and number of formal research presentations (p < 0.001) completed during residency. In total, 86% of residents planning to pursue fellowship training had a mean number of publications and presentations during residency of 1.25 ± 0.37 and 2.25 ± 0.54, respectively. Interpretation: Level of PGY significantly affected quantitative scholarly activity, but the numbers and types of presentations performed prior to residency, completion of an honours or graduate degree and plans to pursue fellowship training did not.